2023
DOI: 10.3390/diagnostics13020258
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of Radiomic Features: Two-Dimensional versus Three-Dimensional MRI-Based Feature Reproducibility in Lipomatous Soft-Tissue Tumors

Abstract: This retrospective study aimed to compare the intra- and inter-observer manual-segmentation variability in the feature reproducibility between two-dimensional (2D) and three-dimensional (3D) magnetic-resonance imaging (MRI)-based radiomic features. The study included patients with lipomatous soft-tissue tumors that were diagnosed with histopathology and underwent MRI scans. Tumor segmentation based on the 2D and 3D MRI images was performed by two observers to assess the intra- and inter-observer variability. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Tumor region of interests (ROIs) were drawn on the entire volume of the lesion. Additionally, a reference region of interest (ROI) was drawn in fat on T1W MRI for image-intensity-normalization procedure [ 24 ]. All cases were selected randomly and blindly for repetitive the segmented ROI by two observers (statistician and research scientist) and subsequently confirmed their precision by experts in musculoskeletal radiology and orthopedic oncology.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tumor region of interests (ROIs) were drawn on the entire volume of the lesion. Additionally, a reference region of interest (ROI) was drawn in fat on T1W MRI for image-intensity-normalization procedure [ 24 ]. All cases were selected randomly and blindly for repetitive the segmented ROI by two observers (statistician and research scientist) and subsequently confirmed their precision by experts in musculoskeletal radiology and orthopedic oncology.…”
Section: Methodsmentioning
confidence: 99%
“…The purpose of this step was to adjust for differences in T1W MRI protocols. The normalized intensity value (NIV) [ 24 ] was determined as follows: .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether 3D approaches generate more consistent radiomics results is still debated, with some publications in sarcoma imaging asserting superiority of 3D segmentation versus 2D segmentation techniques. [24][25][26][27] Image segmentation can be performed with manual delineation of a lesion, semiautomatic segmentation approaches with reduced need for direct user interaction, or with completely automated segmentation procedures. Fully automated image segmentation in sarcoma is still an area of active research with reliable validated automatic segmentation techniques holding the promise of increased speed and reproducibility of tumor segmentations without the need for time-intensive manual or semiautomated segmentation techniques or intra-and interrater variability assessments.…”
Section: The Radiomic Workflowmentioning
confidence: 99%
“…Particularly needed are predictive modeling techniques that can provide accurate results to help decision-making. Logistic regression is one of the techniques that is widely employed in data analysis and machine learning communities [1][2][3][4]. This predictive modeling technique describes the relationships between independent and outcome variables and predicts the outcome variables' future values [5,6].…”
Section: Introductionmentioning
confidence: 99%